2017
DOI: 10.1080/17460441.2017.1280456
|View full text |Cite
|
Sign up to set email alerts
|

Screening-based approaches to identify small molecules that inhibit protein–protein interactions

Abstract: Protein-protein interactions (PPIs) are very attractive targets for drug development as they play important roles in regulating many aspects of pathophysiologies. It has recently been revealed that the functionally important region of most PPIs is small enough to be modulated by small molecules. Thus, many studies in this field have achieved amazing progress, together with diverse and advanced screening technologies. Areas covered: This article presents screening technologies to identify small molecule inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 102 publications
0
19
0
Order By: Relevance
“…In addition to enzymatic biochemical screens, new cell-free technologies have recently emerged that allow for the direct interrogation of the interaction between biomolecules and small molecules in the context of a high throughput NPD screen. [153][154][155] For many disease-associated molecular targets that are not enzymes but do have structural features that can be probed for small molecule binding biophysical screening techniques are useful. Since these newly developed HTS technologies do not rely on biochemically catalyzed reactions but rather on a physical interaction between the small molecule and the target protein/nucleic acid, they are considered biophysical high throughput assays.…”
Section: Non-enzymatic Biochemical Screensmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to enzymatic biochemical screens, new cell-free technologies have recently emerged that allow for the direct interrogation of the interaction between biomolecules and small molecules in the context of a high throughput NPD screen. [153][154][155] For many disease-associated molecular targets that are not enzymes but do have structural features that can be probed for small molecule binding biophysical screening techniques are useful. Since these newly developed HTS technologies do not rely on biochemically catalyzed reactions but rather on a physical interaction between the small molecule and the target protein/nucleic acid, they are considered biophysical high throughput assays.…”
Section: Non-enzymatic Biochemical Screensmentioning
confidence: 99%
“…153,155,159 Among the earliest high throughput biophysical drug discovery assays was the scintillation proximity assay (SPA). 142,154 An early iteration of this microbead based assay used target protein coated scintillant microbeads and radiolabeled ligands to detect substances that interfered with the target-ligand interaction, detectible as a decrease in bead (target) dependent scintillation. As the eld moved away from radiolabeled ligands the SPA was replaced with Förster Resonance Energy Transfer (FRET) based bead dependent assays, such as the LANCE format, whereby a lanthanide containing microbead coated with one member of an interacting pair was incubated with a complimentary FRET acceptor labeled interactor and then probed with a chemical library to nd substances that competed with this interaction.…”
Section: Non-enzymatic Biochemical Screensmentioning
confidence: 99%
See 1 more Smart Citation
“…Many protein‐protein interactions (PPIs) regulate the disease state; therefore targeting the PPIs is crucial for drug discovery . Usually, the PPI‐interacting surfaces are large, flat, and lack the deep and well‐defined binding cavities.…”
Section: Introductionmentioning
confidence: 99%
“…9,17,19,20 Many protein-protein interactions (PPIs) regulate the disease state; therefore targeting the PPIs is crucial for drug discovery. 12,14,[21][22][23][24] Usually, the PPI-interacting surfaces are large, flat, and lack the deep and well-defined binding cavities. However, mutational analyses of PPI interfaces revealed that the binding affinity is not evenly distributed across the binding interfaces, but instead contributed by the small patch of amino acid residues know as hot spot.…”
mentioning
confidence: 99%